Positive role of cell wall anchored proteinase PrtP in adhesion of lactococci - Buist Girbe; Bellon-Fontaine Marie-Noëlle; Juillard Vincent; Le Goff Carine; Habimana Olivier; Kulakauskas Saulius; Briandet Romain (BMC Microbiology, 2007)
Abstract Background The first step in biofilm formation is bacterial attachment to solid surfaces, which is dependent on the cell surface physico-chemical properties. Cell wall anchored proteins (CWAP) are among the known adhesins that confer the adhesive properties to pathogenic Gram-positive bacteria. To investigate the role of CWAP of non-pathogen Gram-positive bacteria in the initial steps of biofilm formation, we evaluated the physico-chemical properties and adhesion to solid surfaces of Lactococcus lactis. To be able to grow in milk this dairy bacterium expresses a cell wall anchored proteinase PrtP for breakdown of milk caseins. Results The influence of the anchored cell wall proteinase PrtP on microbial surface physico-chemical properties, and consequently on adhesion, was evaluated using lactococci carrying different alleles of prtP. The presence of cell wall anchored proteinase on the surface of lactococcal cells resulted in an increased affinity to solvents with different physico-chemical properties (apolar and Lewis acid-base solvents). These properties were observed regardless of whether the PrtP variant was biologically active or not, and were not observed in strains without PrtP. Anchored PrtP displayed a significant increase in cell adhesion to solid glass and tetrafluoroethylene surfaces. Conclusion Obtained results indicate that exposure of an anchored cell wall proteinase PrtP, and not its proteolytic activity, is responsible for greater cell hydrophobicity and adhesion. The increased bacterial affinity to polar and apolar solvents indicated that exposure of PrtP on lactococcal cell surface could enhance the capacity to exchange attractive van der Waals interactions, and consequently increase their adhesion to different types of solid surfaces and solvents.